Impact of Al–Tl co-doping on the optoelectronic properties of ZnO thin film: Experimental and DFT approach - Kumar A.; Gorai D.K.; Kumar B.; Kundu T.K.; Ahmad M.I. (My University, 2025)
Thallium (Tl) and aluminium (Al) co-doping and radiative annealing in a 5 % hydrogen (H2) and 95 % argon (Ar) atmosphere for 80 s were utilized to enhance the electrical and optical properties of the ZnO transparent conductive oxide (TCO) thin film. It was observed that solution-processed 2 at % Al and 0.5 at % Tl co-doped ZnO (TAZO) films have wurtzite structure with (002) orientation. The radiative annealing in a 5 % H2 atmosphere results in the passivation of defects. Tl and Al co-doping significantly improves the electronic properties, crystallinity, morphology, transmittance, charge mobility, and conductivity of the ZnO thin film. A resistivity as low as ∼4.6 x 10−4 Ω-cm along with ∼92 % transparency was achieved in the 2 %Al-0.5 %Tl co-doped ZnO film. The density functional theory (DFT) calculations also showed mobility and electron density enhancement on co-doping Tl and Al in ZnO thin film. Reduced absorption coefficient and higher mobility after co-doping of Al and Tl can be beneficial for second and third-generation photovoltaic solar cells. © 2025 Elsevier B.V.